ANALISIS PERSEPSI MASYARAKAT UMUM TERHADAP PRODUK INVESTASI SYARIAH DAN KEPUTUSAN UNTUK BERINVESTASI - Emilia Septiani; Budi Santoso; Mulyadi Mulyadi; Muhdin Muhdin (Distribusi - Journal of Management and Business, 2018)
The purpose of this study were to determine the general public perception of Mataram City in terms of products and financial institutions that provide sharia investment products and decisions society to invest in sharia products. Data collection method used in this research is sample survey. Sampling technique in this research use purposive sampling with amount of sample counted 100 people. The analytical tools used in this research are the public perception index and decision-making was based on ‘Yes’ or ‘No’ answeared from the respondents. The result of this study showed that the perception of the general public in the city of Mataram toward sharia investment products is good. In spite of the people are still have doubt about the sharia principles used by Islamic financial institutions, both bank financial institutions or non-bank financial institutions. For investment decisions, from 100 respondent, 58 people decided to invest sharia products.